Zahnloser Tiger. Warum im ÖPNV nur wenig Marketing betrieben wird. - Rumpke, Christian A. (Deutscher Verkehrs-Verl., 2007)
Die Kürzung öffentlicher Zuschüsse lässt im ÖPNV derzeit den Ruf nach "mehr Marketing" laut werden. Mit dessen Hilfe sollen Mobilitätsdienstleister in Deutschland ihre Fahrgelderlöse steigern und so zumindest einen Teil der entstehenden Einnahmelücke schließen. Tatsächlich kann nachgewiesen werden, dass die Marktakteure bislang viele der verfügbaren Instrumente der Leistungs-, Preis-, Kommunikations- und Distributionspolitik nicht oder nur suboptimal einsetzen. Ursache hierfür ist, dass der Nutzung des an sich wirksamen Marketingspektrums organisatorische Hürden im Weg stehen. Erst wenn die zwischen Verkehrsunternehmen und Verkehrsverbünden gewachsene Struktur radikal verändert wird, können Marketinginstrumente zur Entschärfung der finanziell desolaten Situation im ÖPNV beitragen. Der Aufsatz basiert auf einer Dissertation des Autors zum gleichen Thema. difu

In the public transport market in Germany local and regional authorities, which have so far massively subsidised public transport, are successively withdrawing from their financial commitments. For mobility service providers, this means that farebox revenues are becoming more important, with increasing reliance on financing by passengers. Service marketing offers effective leverage through product, price, promotion and place policy. The article and the underlying study critically examine whether public transport actors exploit these dimensions to their full extent and whether they are in a position to do so. A content analysis of Internet presences reveals how marketing in the public transport field is implemented in practice. The analysis focuses on the 23 largest urban transport undertakings in Germany and related transport associations. The findings thus generated are verified by means of expert interviews with marketing officials. In this way also the question is examined why certain marketing tools areused not at all or only rudimentarily. Symptoms are not only identified but their causes investigated. In sum it can be said that deploying the spectrum of essentially effective marketing tools is hampered by organisational obstacles: overlapping competencies among a multitude of padicipating actors, false incentives, and public political influence. On this basis, the article explicates concrete consequences. Deploying the marketing tooibox can effectively contribute to easing the deplorable financial situation in German public transport only if market actors radically reform their current organisational interrelations. To that marketing tools and functions should be brought together within one marketing company which is owned by operators and in which responsibilities for costs and proceeds are linked. difu
Keywords: Verkehr; ÖPNV; Marketing; Empirische Sozialwissenschaft; Befragung; Verkehrsunternehmen; Verkehrsverbund; Preispolitik; Experteninterview; Marke; Verkaufsförderung; Anreiz; Einflussnahme; Kostenverantwortung